Metabolic, Inflammatory and Imaging Biomarkers in Evaluation of Coronary Arteries Anatomical Stenosis in Patients with Stable Coronary Artery Disease - O. A. Koshelskaya; T. E. Suslova; I. V. Kologrivova; N. Y. Margolis; O. A. Zhuravleva; O. A. Kharitonova; I. V. Vinnitskaya (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To reveal the statistically significant determinants of the coronary artery (CA) stenosis ≥70% in patients with chronic stable CA disease receiving drug therapy.Material and methods. The study included 68 patients (aged 59.6±6.4 years) with stable CA disease and optimal cardioactive therapy. Coronary angiography was performed in all patients. Basic serum parameters of carbohydrate and lipid metabolism were evaluated; serum concentration of cytokines, adipokines and high sensitive C-reactive protein (hsCRP) were determined by ELISA. The epicardial adipose tissue (EAT) thickness was measured by B-mode echocardiography.Results. The patients’ classification model was created. It allowed to determine probability P for CA stenosis of 70% or more for each patient using formula Р, where L=0.89-1.09×gender+ 0.51×triglycerides–0.28×HDL+0.24×hsCRP (HDL – high density lipoproteins). If calculated P value falls into interval (0; 0.228) the patient should be classified into the group with the risk of CA stenosis ≥70%, while if calculated P value falls into interval (0.228; 1), the patient should be classified into group with CA stenosis below 70%. Even though EAT thickness was indistinguishable determinant of CA stenosis ≥70% in our study, its inclusion into the model as a fifth variable allowed to increase the model quality: area under ROC-curve (AUC) in the model without EAT thickness constituted 0.708 (p=0.009), and increased up to 0.879 (p=0.011) after EAT thickness inclusion.Conclusions. Male sex, level of triglycerides, HDL and hsCRP are statistically significant determinants of CA stenosis ≥70%. The presence of the triglycerides level in the created model underscores an important contribution of this lipid fraction, even when elevated only up to the moderate values, into modulation of the residual cardiovascular risk in patients receiving statins.